Δ47-Δ48 systematics of speleothem carbonate - Jens Fiebig; Christoph Spötl; Ana Moreno; Haiwei Zhang; Miguel Bernecker; Philip Staudigel; Allison Curley; Anna Nele Meckler; Monika Markowska; Julian Schröder; Hubert Vonhof (Geochimica et Cosmochimica Acta, 2026)

Spotlight: Lō`ihi Seamount - Hubert Staudigel; Craig Moyer; Michael Garcia; Alex Malahoff; David Clague; Anthony Koppers (Oceanography, 2010)

Spotlight: Jasper Seamount - Jasper Konter; Hubert Staudigel; Jeffrey Gee (Oceanography, 2010)

Seamount Sciences: Quo Vadis? - Hubert Staudigel; Anthony Koppers; J. William Lavelle; Tony Pitcher; Timothy Shank (Oceanography, 2010)

Seamounts in the Subduction Factory - Hubert Staudigel; Anthony Koppers; Terry Plank; Barry Hanan (Oceanography, 2010)

From the Guest Editors - Hubert Staudigel; Anthony Koppers; J. William Lavelle; Tony Pitcher; Timothy Shank (Oceanography, 2010)

Seamount Catalog: Seamount Morphology, Maps, and Data Files - Anthony Koppers; Hubert Staudigel; Ruper Minnett (Oceanography, 2010)

Defining the Word "Seamount" - Hubert Staudigel; Anthony Koppers; J. William Lavelle; Tony Pitcher; Timothy Shank (Oceanography, 2010)

Spotlight: Vailulu’u Seamount - Anthony Koppers; Hubert Staudigel; Stanley Hart; Craig Young; Jasper Konter (Oceanography, 2010)

Seamount Mineral Deposits: A Source of Rare Metals for High-Technology Industries - James Hein; Tracey Conrad; Hubert Staudigel (Oceanography, 2010)

The Geological History of Deep-Sea Volcanoes: Biosphere, Hydrosphere, and Lithosphere Interactions - Hubert Staudigel; David Clague (Oceanography, 2010)

An interlaboratory comparison of 16S rRNA gene‐based terminal restriction fragment length polymorphism and sequencing methods for assessing microbial diversity of seafloor basalts - Beth Orcutt; Brad Bailey; Hubert Staudigel; Bradley M. Tebo; Katrina J. Edwards (Environmental Microbiology, 2009)
Summary We present an interlaboratory comparison between full‐length 16S rRNA gene sequence analysis and terminal restriction fragment length polymorphism (TRFLP) for microbial communities hosted on seafloor basaltic lavas, with the goal of evaluating how similarly these two different DNA‐based methods used in two independent labs would estimate the microbial diversity of the same basalt samples. Two samples were selected for these analyses based on differences detected in the overall levels of microbial diversity between them. Richness estimators indicate that TRFLP analysis significantly underestimates the richness of the relatively high‐diversity seafloor basalt microbial community: at least 50% of species from the high‐diversity site are missed by TRFLP. However, both methods reveal similar dominant species from the samples, and they predict similar levels of relative diversity between the two samples. Importantly, these results suggest that DNA‐extraction or PCR‐related bias between the two laboratories is minimal. We conclude that TRFLP may be useful for relative comparisons of diversity between basalt samples, for identifying dominant species, and for estimating the richness and evenness of low‐diversity, skewed populations of seafloor basalt microbial communities, but that TRFLP may miss a majority of species in relatively highly diverse samples.